La traduction intersémiotique ou comment traduit-on des images? - Tomaszkiewicz, Teresa (Neophilologica, 2006)
In her article Teresa Tomaszkiewicz compares the mechanism appearing during the interlinguistic and intersemiotic translation. Contrary to appearances, it seems that the transfer of meaning of an expression produced in one natural language into a text in another language has a lot in common with the transfer of meaning through non-linguistic means e.g. various types of images. The author compares the functioning of images with such linguistic forms as concepts, predicates, expressions and descriptions. She analyzes various types of relations that are created between linguistic elements and images in order to convey the meaning of these images. These relations are: equivalence, parallelism, complementarity, interpretation and contrariness.